Potential role of apple wood biochar in mitigating mercury toxicity in corn (Zea mays L.) - Qahreman Abbasi; Latifeh Pourakbar; Sina Siavash Moghaddam (Ecotoxicology and Environmental Safety, 2023)
Mercury (Hg) is a very toxic decomposition-resistant metal that can cause plant toxicity through bioaccumulation and oxidative damage. Biochar, derived from organic waste and agricultural garbage, is an on-site modification technique that can improve soil health in heavy metals-polluted regions. The present experiment was designed to explore the role of apple biochar in the management of mercury toxicity in corn (Zea mays cv. ‘PL535’). Different levels of biochar derived from apple wood (0%, 2.5%, 5.0%, and 7.5% w/w) along with different Hg concentrations (0, 20, 40, and 60 mg/L) were used in the experiment that was based on a completely randomized design. Based on the results, HgCl2 at all rates reduced root and shoot dry weight and length, tolerance index, chlorophyll a and b content, the Hill reaction, and dissolved proteins and increased shoot and root Hg content (up to 72.57 and 717.56 times, respectively), cell death (up to 58.36%), MDA level (up to 47.82%), H2O2 (up to 66.33%), dissolved sugars, and proline. The results regarding enzymatic and non-enzymatic antioxidants revealed increases in total phenol and flavonoids content (up to 71.27% and 86.71%, respectively), DPPH free radical scavenging percentage, and catalase (CAT) and ascorbate peroxidase (APX) activity (up to 185.93% and 176.87%, respectively), in corn leaves with the increase in the Hg rate applied to the culture medium. The application of biochar to the substrate of the Hg-treated corns reduced Hg bioavailability, thereby reducing Hg accumulation in the roots (up to 76.88%) and shoots (up to 71.79%). It also reduced the adverse effect of Hg on the plants by increasing their shoot and root dry weight, photosynthesizing pigments, Hill reaction, and APX activity and reducing cell death, H2O2 content, and MDA content. The results reflected the capability of apple wood biochar at all rates in reducing Hg bioavailability and increasing Hg fixation in Hg-polluted soils. However, it was most effective at the rate of 7.5%.